Níveis de inóculo de Sclerotinia sclerotiorum em sementes de soja tratadas com fungicidas e agentes biológicos - Ferreira, Thiago Costa (2015)
The white mold, caused by S. sclerotiorum on soybean can be spread by seed, with little information on seed treatment to control it. In this study, the effects of chemical and biological treatments were evaluated for the control of S. sclerotiorum associated with soybean seeds in different inoculum potentials under controlled conditions. The different inoculum potentials P0, P24, P48, P72 and P96, corresponding to 0, 24, 48, 72 and 96 hours of exposure to the pathogen seeds were obtained by water restriction technique. The inoculated seeds were treated with methyl thiophanate + fluazinam, T.harzianum and T. asperellum separately. Sanity, germination and vigor of seeds and seedlings were evaluated. The trial was conducted at 20 °C and 25 °C. In vitro testing, pathogen control occurred only with the use of chemical fungicides in P24 inoculum potential. It was not detected the disease in potential P0. At 20 °C the effects of disease were more drastic and the effectiveness of sanitary treatment was lower in both treatments. In general, T. harzianum was more effective in the control of the disease than T. asperellum, although under epidemiological point of view the differences were not significant. It concluded that the sanitary treatment of seeds to control white mold from contaminated soybean seeds has become effective at low inoculum potential conditions (P24).